Model Tempat Sampah Lukis dan Bersuara “Schabi” terhadap Pengetahuan dan Ketepatan Memilah Sampah pada Siswa Kelas 5 Sekolah Dasar Di Banyuraden, Gamping, Sleman - Nadiya Fahriani; Bambang Suwerda; Achmad Husein (Poltekkes Kemenkes Yogyakarta, 2018)
Waste management with new paradigm and supplying facility of waste sorting should have been started in schools. However, elementary schools in Banyuraden have not implemented those two things appropriately. Painted and voiced trash bin “Schabi” is made to give knowledge to and sti-mulate student for sorting their waste accurately. The purpose of this research was to know whe-ther this waste bin model is advantageous for students’ knowledge and accuracy about waste sorting. The study was an experiment with post-test only control group design. The study popu-lation was all five-grade students in Banyuraden, Gamping, Sleman; and as the sample were five grade students of Patran Elementary School as the treatment group and five grade students of Kanoman Elementary School as the control group. Result of the study show that the average knowledge score in the treatment grup was 9,5 and in the control group it was 7,3. The average score for accuracy in the treatment group was 2,63 and in the control group it was 1,68. The data analyses by using Man Whitney statistical test at ?=0,05 obtained a p-value <0,001. Therefore, it can be concluded that “Schabi” painted and voiced trash bin model affect the knowledge and accuracy of student in waste sorting with accordance to trash types instruction, i.e. leaves and leftover, paper waste, and plastic waste.